VARIASI SOMAKLONAL TANAMAN KANTONG SEMAR (NEPENTHES MIRABILIS DAN N. GRACILIS) SECARA IN VITRO DENGAN MUTAGEN KIMIA KOLKISIN - FITRI DAMAYANTI; IKA ROOSTIKA (Faktor Exacta, 2015)
Nepenthes are potential to be commercialized because of the shape and color of their unique pitcher. Generally, people are interested in new and rare types which have unique color, shape, and size of pitcher.  However, the increase of its demand has led to the decrease of natural populations due to overexploitation in the natural habitats in Indonesian forests without sufficient cultivation or replacement efforts. The genetic erosion has resulted in low level variation of this species. In vitro plant breeding can be carried out through somaclonal variation. The objective of this study was to obtain somaclonal variation method by using colchicin as a chemical mutagen. In vitro shoot of N. mirabilis and N. gracilis were used in this research as explant that planted in ¼ MS + colchicin at the level of 0, 0.05, 0.075, and 0,1%. The application of colchicin could produced cultures with high level of growth than control. The best result was obtained from colchicin at a level of 0.05% as a alternative in vitro to improve genetic variation. Key words: N. mirabilis, N. gracilis, somackonal variation, colchicin